Perceived Benefits And Perceived Behavioral Control Toward Fintech Adoption Intention In Banking Products - Marco, Michael; Arifin, Agus Zainul (LPPM ISNJ Bengkalis, 2024)
This study aims to verify the relationship between perceived benefits and perceived behavioral control on fintech adoption intention on banking products and services in Indonesia. This quantitative study uses the technology acceptance model (TAM) approach and the theory of planned behavior (TPB). The sampling technique uses purposive sampling, with a sample size of 545 respondents. The data source used is primary data. Data were collected by distributing questionnaires built using Google Forms and distributed through social media. The data analysis technique uses a structural equation model based on partial least squares (SEM-PLS) with the help of SmartPLS software. The study's results prove that perceived benefits and perceived behavioral control positively affect fintech adoption intention. This study can theoretically prove that the TAM and TPB theories can be applied together and explain the relationship between research variables. Practically, the TAM and TPB theories can be used together as a policy-making model for implementing fintech innovation in banking.